Impaired inhibition of epileptiform activity by baclofen, but not by adenosine in the weaver hippocampus - Jarolimek, Wolfgang; Bäurle, Jörg; Misgeld, Ulrich (Neuropharmacology, 2000)
The weaver defect results in a loss of baclofen- and adenosine-gated K+ conductance in the hippocampus of adult homozygous (wv/wv) mice. In addition, suppression of hippocampal epileptiform activity by baclofen is impaired (Jarolimek, W., Bäurle, J., Misgeld, U., 1998. Pore mutation in a G protein-gated inwardly rectifying K+ channel subunit causes loss of K+ dependent inhibition in weaver hippocampus. Journal of Neuroscience 18, 4001-4007). We used wv/wv and wild-type (+/+) mice to determine whether K+ conductance increases are essential for the suppression of epileptiform activity by R-baclofen and adenosine in disinhibited hippocampal slices. In wv/wv mice R-baclofen was less potent by two orders of magnitude in reducing the frequency of spontaneous synchronous burst discharges than in +/+ mice. Endogenous adenosine and adenosine A1 receptor agonists differed only slightly in their efficacy to inhibit spontaneous synchronous burst discharges in wv/wv and +/+ mice. The findings on adenosine A1 receptors suggest that the varied efficacy of R-baclofen in wv/wv and +/+ mice may not be explained solely on the basis of a loss of ligand-gated K+ conductance. Therefore, we investigated the affinity of GABAB receptors for the antagonist CGP55845A in wv/wv and +/+ hippocampi. Schild plot analysis revealed a KD for the GABAB antagonist CGP55845A 10 fold higher in wv/wv than in +/+ mice. The data suggest that an alteration of GABAB receptors could contribute to the reduced efficacy of R-baclofen to suppress hippocampal epileptiform activity in weaver mice, while the suppression by adenosine remains largely unaffected.